Prevalence of hypomagnesemia in children admitted to pediatric intensive care unit and its correlation with patient outcome - Dandinavar, Siddappa F.; D., Suma; Ratageri, Vinod H.; Wari, Prakash K. (International Journal of Contemporary Pediatrics, 2019)
Background: Magnesium deficiency is common in critical illness and is said to be associated with increased need for mechanical ventilation, mortality and prolonged ICU stay. The knowledge of hypomagnesemia is essential as available data is scarce and it could have prognostic and therapeutic implications. This study was undertaken to estimate the prevalence of hypomagnesemia at the time of admission in PICU and its correlation with length of PICU stay, duration on mechanical ventilator and outcome at the end of hospital stay-death or discharge. Methods: This is a prospective observational study including 343 children aged 1month to 12years admitted to PICU. Detailed history taking and clinical examination was done for all enrolled children. At admission, blood was collected for estimation of serum magnesium. Patients were categorized into three groups i.e., hypomagnesemia, normomagnesemia and hypermagnesemia and data was analysed. Results: Out of 343 children, 28% had hypomagnesemia, 7.3% had hypermagnesemia and 64.7% had normomagnesemia. Hypomagnesemia was more common in neurological disorders. No association was found between magnesium and length of mechanical ventilation. PICU stay was significantly longer in hypomagnesemia group (p=0.031). 37.5% patients with hypomagnesemia also had hypocalcemia and 35.4% had hypokalemia. Mortality rate was higher in those with hypomagnesemia (30.2%) compared to those with normomagnesemia (22.1%). Conclusions: Patients with hypomagnesemia had increased duration of PICU stay, other associated electrolyte abnormalities and higher mortality. Hence monitoring of magnesium levels in critically ill patients is indicated.